Long-term monitoring of sediment runoff for an active sediment control in Joganji River - Miwa Kenji; Mikami Koso; Nagayama Takahiko; Furuya Tomohiko; Hayashi Seiya; Fujita Masaharu; Miyata Syusuke; Satofuka Yoshifumi; Mizuyama Takahisa; Miyamoto Kuniaki; Ikeda Akihiko; Itoh Takahiro (E3S Web of Conferences, 2023)
There were huge sediment yielding and deposition due to debris flows by breaking natural landslide dams which were formed by earthquake in 1858 at upstream reach of Joganji River. Sediment transportation is still active by debris flow and flow with bedload due to rainfall, though a lot of erosion control dams have been constructed. Continuously measuring sediment runoff for long term along a main river is necessary to evaluate the propagation of sediment after the huge events for sediment management in the basin using well hydrological information. Appropriate tools are selected and applied to monitoring in the area managed by Tateyama Mountain Area Sabo Office along Joganji River, using a Reid-type bedload slot sampler, robust-type hydrophone and velocity meter on the bed for bedload and turbidity meter for washload. Monitored data is concentratedly collected at the office to apply risk management for sediment movement due to heavy rainfall and so on. Several typical data and problems to solved were shown because it passed around twenty years since sediment monitoring started, and those are reported in present study.